The tacit knowledge dimension for knowledge management in higher education organizations / Mizan Hitam, Sabariah Mahat and Rajasegaran K. - Hitam, Mizan; Mahat, Sabariah; K., Rajasegaran (Research Management Institute (RMI), 2008)
Knowledge is the icon of the new economy. It is now touted as the most likely source of competitive advantage. Therefore, knowledge management (KM) is seen as an innovation with the potential to affect the whole of an organizations business. Being in the knowledge business, higher education organizations (HEOs) are not an exception to this imperative more so when there is a long history of HEOs successfully adopting management philosophies from the business world. However, KM in HEOs has not caught the attention of mainstream KM researchers and this qualitative study was an attempt to fulfill this research niche. The purpose ofthis paper is to explore the nature of knowledge to be incorporated in the knowledge base of HEOs, A major mode of data collection in this study was through face-to face interviews. Twenty lecturers were interviewed. The results demonstrate that the nature of explicit knowledge in HEOs relates to the organization, the people in authority, the various offices, bursary, library, faculties, staff portal, student portal, and other relevant information. Tacit knowledge is concerned with issues and mailers relating to students, lecturers' beliefs towards teaching, interacting with members in the organization and managing organizational constraints.